Returns to private equity: idiosyncratic risk does matter! - Elisabeth Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Owners of private companies often invest a substantial share of their net worth in one company, which exposes them to idiosyncratic risk. For US companies we investigate whether owners require compensation for lack of diversification in the form of higher returns to equity. Exposure to idiosyncratic risk is measured as the share of the owner's net worth invested in the company. Equity returns are measured as the earnings rate and as capital gains. For both returns measures we find a positive and significant influence of exposure to idiosyncratic risk. This paper improves our understanding of returns to private equity.
Older version: http://hdl.handle.net/10419/24054
Keywords: G32; G11; L26; 330; returns to private equity; exposure to idiosyncratic risk; private companies; Klein- und Mittelunternehmen; Unternehmer; Investition; Portfolio-Management; Rentabilität; Ökonomischer Anreiz; Schätzung; USA